2018
DOI: 10.1038/s41467-018-07206-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Greenland ice sheet driven by pCO2 variations across the Pliocene Pleistocene transition

Abstract: It is generally considered that the perennial glaciation of Greenland lasting several orbital cycles began around 2.7 Ma along with the intensification of Northern Hemisphere glaciation (NHG). Both data and model studies have demonstrated that a decline in atmospheric pCO2 was instrumental in establishing a perennial Greenland ice sheet (GrIS), yet models have generally used simplistic pCO2 constraints rather than data-inferred pCO2 evolution. Here, using a method designed for the long-term coupling of climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…Even for changes as recent as the mid-Holocene, there is a debate, for example, over whether the abrupt desertification of the Sahara is due to a bifurcation, as suggested in Claussen et al (1999) using an Earth model of intermediate complexity (EMIC), or is a transient response of the AMOC to a sudden termination of freshwater discharge to the North Atlantic, as proposed in Liu et al (2009), using a coupled atmosphere-ocean GCM (AOGCM). Similarly, for the glaciation of Greenland at the Pliocene-Pleistocene transition, recent work in Tan et al (2018), using a coupled GCM-ice-sheet model, shows good agreement with proxy records without the need for bifurcations. The model of this paper does not adapt to these two situations, which are localized and away from the poles where the axis of symmetry restricts the dynamics and facilitates the analysis presented here.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Even for changes as recent as the mid-Holocene, there is a debate, for example, over whether the abrupt desertification of the Sahara is due to a bifurcation, as suggested in Claussen et al (1999) using an Earth model of intermediate complexity (EMIC), or is a transient response of the AMOC to a sudden termination of freshwater discharge to the North Atlantic, as proposed in Liu et al (2009), using a coupled atmosphere-ocean GCM (AOGCM). Similarly, for the glaciation of Greenland at the Pliocene-Pleistocene transition, recent work in Tan et al (2018), using a coupled GCM-ice-sheet model, shows good agreement with proxy records without the need for bifurcations. The model of this paper does not adapt to these two situations, which are localized and away from the poles where the axis of symmetry restricts the dynamics and facilitates the analysis presented here.…”
Section: Introductionmentioning
confidence: 61%
“…They concluded that falling CO 2 levels were primarily responsible for the formation of the Greenland ice sheet in the late Pliocene. Recently, Tan et al (2018) have strengthened this conclusion.…”
Section: Ebm For the Pliocene Paradoxmentioning
confidence: 90%
See 2 more Smart Citations
“…Atmospheric concentrations of CO 2 can be retrieved from Antarctic ice core records back to about 850 ka (e.g., [36]) ( Figure 1). However, a recent study shows that uncertainties in CO 2 reconstruction of the Late Pleistocene are non-negligible [59], leading to large differences between models, especially in the case of ice sheet glaciation and deglaciation thresholds [60]. For pre-ice-core records, CO 2 reconstructions are retrieved from sediment cores, with large uncertainties (Figure 1, e.g., [39]).…”
Section: Current Challengesmentioning
confidence: 99%